Bioherbicidal potential of Rumex crispus infected with Didymella rumicicola - Bhat, K. A.; Malik, G. M.; Akhtar, S. (Journal of Phytology, 2023)
A new foliar disease was observed on a perennial weed Rumex crispus which grows extensively in orchards, pastures, hay crops, lawns and home gardens in Kashmir valley. Repeated Isolation of the pathogen from the infected leaves of Rumex crispus yielded the fungus which on the basis of Cultural and morphological characteristics showed a resemblance to Didymella sp. Pathogenicity was confirmed by the detached leaf technique as well as inoculating whole plants in pots. Precise confirmation of the identity of the pathogen was done by sequencing the reference genes using ITS1 and ITS4 markers and sequenced data was subjected to BLAST which showed 99.80 per cent similarity with Didymella rumicicola which was previously only reported in New Zealand on Rumex obtusifolius prior to this study. Host range, as well as bioherbicidal potential of this pathogen on hosts of five different families of cultivated crops along with Rumex plants, revealed that no disease incidence was found on host plant species of other families of cultivated crops, whereas,100% disease incidence and 80% severity were observed on Rumex crispus at 15 and 25 days after inoculation respectively. Physiological studies showed the newly isolated pathogen Didymella rumicicola showed the best radial growth on Potato dextrose agar at pH 6.5 and at a temperature of 25oC.